The Role of Brand Image in Mediating Sales Promotion and Perceived Ease of Use Toward Purchase Decisions for Fashion Products Among Zalora Marketplace Consumers in Jember - Ardini Manzilatun Nikmah; Raden Andi Sularso; Bambang Irawan (Nomico, 2025)
This study aims to analyze the influence of sales promotion and perceived ease of use on purchasing decisions of fashion products among Zalora consumers in Jember, with brand image as a mediating variable. This research employs a quantitative approach by distributing questionnaires to respondents who have made purchases through the Zalora platform. Data were analyzed using Partial Least Square (PLS) to examine both the structural model and measurement model, enabling evaluation of direct and indirect relationships among the research variables. The results indicate that sales promotion and perceived ease of use have a positive and significant influence on purchasing decisions. Furthermore, sales promotion and perceived ease of use are found to positively affect brand image. The findings also show that brand image significantly influences purchasing decisions. Mediation testing confirms that brand image mediates the relationship between sales promotion and perceived ease of use on purchasing decisions, demonstrating the strategic role of brand image in strengthening the impact of marketing stimuli and digital platform experience on consumer purchasing decisions on Zalora in Jember.